The Report of the Universidad de Valladolid of 1938 on the “Red-Separatist” Domination in the Basque Provinces. Counter-propaganda of the Bombing of Guernica - Velasco San Pedro, Luis Antonio (CIAN-Revista de Historia de las Universidades, 2023)
The work analyzes the barely known Report of the University of Valladolid of 1938 on the «red-separatist» domination in the Basque Provinces, and tries to answer the questions of why and what for it was made, who were the promoters and authors, who financed it and to whom it was distributed, as well as its content and the message it was trying to convey.
Keywords: History of the University of Valladolid; Spanish Civil War; Basque Country; Bombing of Guernica counter-propaganda; counter-propaganda